Involvement of T Cells in Enhanced Resistance to Klebsiella pneumoniae Septicemia in Mice Treated with Liposome-Encapsulated Muramyl Tripeptide Phosphatidylethanolamine or Gamma Interferon - ten Hagen, Timo L. M. (American Society for Microbiology, 1998)
We have previously shown that prophylactic administration of the liposome-encapsulated immunomodulating agents muramyl tripeptide phosphatidylethanolamine (MTPPE) and gamma interferon (IFN-γ) results in strongly increased survival of mice from a normally lethal septicemia with Klebsiella pneumoniae. It was anticipated that the treatment acts on macrophages and nonspecifically augments host resistance to various infections. In the present study, we provide evidence for a key role for T cells in host defense potentiation by the liposomal immunomodulators toward K. pneumoniae septicemia. It is shown that both CD4 and CD8 cells are important in immunomodulation, most likely due to production of IFN-γ. Depletion of circulating IFN-γ resulted in strong reduction of the antimicrobial host defense activation. Administration of interleukin-10 resulted in decreased antimicrobial host defense activation by liposomal immunomodulators. Moreover, administration of liposomal immunomodulators was shown to induce predominantly T-helper type 1 (Th1) cell populations in the spleen. These findings indicate that immunomodulation with liposomal MTPPE and IFN-γ favors Th1 and NK cell activation.